(untitled) (Indian Journal Of Clinical Practice, 2025)
Hypertension remains a central pathophysiologic contributor to cardiovascular morbidity and mortality. In its earliest stage, the principal endothelial alteration is merely functional and addressed as “endothelial dysfunction”. Flow-mediated dilatation (FMD) of the brachial artery has been widely used as a noninvasive marker to vascular reactivity. Both microalbuminuria and endothelial dysfunction are expressions of an endothelial pathology; however, it is still uncertain whether they are interrelated, or if the two phenomena are caused in parallel by the cardiovascular risk burden. Aim: To study the relationship of brachial artery flow-mediated dilatation (BAFMD) with microalbuminuria in hypertensive subjects. Method: Total 120 subjects were included in the study comprising 80 hypertension cases and 40 controls. All subjects were subjected to anthropometric measurements and routine biochemical tests – hemogram, urea, serum creatinine, liver function test, lipid profile, BAFMD and urinary albumin to urinary creatinine ratio (30-300 mg/g Cr). Conclusion: Mean % FMD was lower in patients with abnormal microalbuminuria compared to normal and this was statistically verified, with p = 0.016, thereby verifying the central hypothesis of this study.